Severe invasive Listeria monocytogenes rhombencephalitis mimicking facial neuritis in a healthy middle-aged man: a case report and literature review. Issue 1 (January 2021) - Cao, Liming; Lin, Yanwei; Jiang, Hongliang; Wei, Jiehong
Neurolisteriosis is a foodborne infection of the central nervous system that is easily misdiagnosed, especially in healthy adults with atypical symptoms. A 50-year-old man presented with a 3-day history of distortion of the oral commissure. Facial neuritis was diagnosed and treated with intravenous dexamethasone. His condition deteriorated rapidly, and he presented with a slow pharyngeal reflex, stiff neck, and signs of peripheral facial paralysis. Brain magnetic resonance imaging revealed multiple ring-enhanced foci in the brainstem. Routine and biochemical cerebrospinal fluid (CSF) analyses showed increased white blood cells and microproteins. Blood culture and high-throughput genome sequencing revealed Listeria monocytogenes DNA in the CSF. Ampicillin, amikacin, and meropenem were administered, and the patient was transferred from the intensive care unit to a standard medical ward after 2 months. The patient could walk and eat normally; however, he required intermittent mechanical ventilation at 11 months after discharge. Although L. monocytogenes meningitis is rare in healthy immunocompetent adults, it must be considered as a differential diagnosis, especially in adults whose conditions do not improve with cephalosporin antibiotic administration. L. monocytogenes rhombencephalitis mimics facial neuritis and develops quickly. Prompt diagnosis is essential for rapid initiation of antibiotic therapy to achieve the best outcome.